Radical Fluoroalkylation of Isocyanides with Fluorinated Sulfones by Visible‐Light Photoredox Catalysis. (19th January 2016) - Rong, Jian; Deng, Ling; Tan, Ping; Ni, Chuanfa; Gu, Yucheng; Hu, Jinbo
Abstract: The radical fluoroalkylation of isocyanides with fluorinated sulfones is enabled by visible‐light photoredox catalysis. A wide range of readily available mono‐, di‐, and trifluoromethyl heteroaryl sulfones can thus be used as efficient radical fluoroalkylation reagents under mild conditions. This method not only describes a new synthetic application of fluorinated sulfones, but also provides a new route to fluoroalkyl radicals.